IMPROVEMENT OF THE LIFE QUALITY FOR LARYNGOPHARYNGEAL REFLUX PATIENTS AFTER RECEIVING PROTON PUMP INHIBITOR (PPI) THERAPY AT THE ENT-KL POLYCLINIC OF UKI HOSPITAL JANUARY 2021 - FEBRUARY 2021 - Marlina, Lina; Poluan, Fransiskus Harf; Zebua, Ribka Liliana (International Journal of Research -GRANTHAALAYAH, 2021)
(LPR) is a condition in which gastric content to the and reaches larynx and pharynx so that mucous membranes of the larynx, pharynx, and other respiratory organs are inflamed. The symptoms of LPR can affect daily activities, resulting in a decrease in the quality of life (QOL) of the patients. Proton Pump Inhibitor (PPI) is the main therapy for patients with LPR. PPI can improve the symptoms experienced by patients with LPR. The objective of this research is to determine the QOL of patients with LPR after receiving PPI. This research’s method is quasi-experimental studies using and post-test design from January 2021 to February 2021, in 18 patients were assessed for QOL scores using RSI. Each patient was administered 30 mg twice daily before meals for 14 days. Two times of observations are done, before therapy and 14 days after therapy. Data analysis using paired sample T-test. The result is that there is a significant improvement in QOL of patients with LPR on RSI scores after 14 days of administration of 30 mg. (p<0,05). It is concluded that PPI significantly improved the QOL of patients with LPR.